A versatile, stimulus-responsive nanoparticle-based platform for use in both sonodynamic and photodynamic cancer therapy. (February 2017) - Nomikou, N.; Curtis, K.; McEwan, C.; O'Hagan, B.M.G.; Callan, B.; Callan, J.F.; McHale, A.P.
Graphical abstract: Abstract: A PLGA-based multifunctional biodegradable nanoparticle platform co-harboring hematoporphyrin and indocyanine green has been developed. In vitro studies demonstrate ultrasound and light stimulated generation of cytotoxic reactive oxygen species. In vivo studies show that the ICG component facilitates nIR fluorescence imaging that demonstrates accumulation of IV- administered nanoparticles in tumours. In vivo studies also demonstrate ultrasound- and light-mediated inhibition of tumour growth in animals treated with the platform. Since the platform consists entirely of clinically-approved agents it could find use in sonodynamic- and photodynamic-based therapies for cancer. Statement of Significance: We describe a biocompatible and biodegradable nanoparticle-based platform for use in sonodynamic and photodynamic therapeutic approaches for the treatment of cancer. The non-toxic nanoparticles produce cytotoxic reactive oxygen species when exposed to ultrasound and/or light at levels that have no impact on tissues. The system is unique in that it is accumulated by tumours within six hours and has the ability to release its sensitising capability while retaining its imaging capability within a therapeutic time frame. The former could enhance dispersion and sensitising capabilities in less permeable tumour tissues and the latter permits the design of therapeutic approaches that minimize collateral damage to normal tissues.